THE CORPORATE MANAGEMENT OF HIGHER EDUCATIONAL ESTABLISHMENT IN THE CONDITIONS OF EDUCATIONAL MODERNISATION - Oksana Kondur (Vasyl Stefanyk Precarpathian National University, 2018)
The actuality of transition to the corporate model of higher educatioal establishments is discussed in the article. The basic social and economic problems of corporate management for establishments that arise up in the conditions of current modernisation of education are investigated in the given article. The fundamental elements of model effective corporate management of educational establishments are distinguished . The role of corporate culture in a management is determined. The development of corporate culture is one of the best indicators that assist the achievement of high level of education and its quality. Democratization of management in higher educational establishments will promote the competitiveness of them. Key words: corporate management, corporate culture, model of management, establishment of higher education.